Evolutionary conservation genetics - d (Oxford : Oxford University Press, 2009)
Conservation genetics focuses on understanding the role of genetic variation for population persistence. This book is about the methods used to study genetic variation in endangered species and whether genetic variation matters in the extinction of species.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ecological genetics; Evolutionary genetics; Conservation biology; Biodiversity; Biodiversity conservation